2018
DOI: 10.1159/000488622
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Receptor for Advanced Glycation End Products (sRAGE) is Up-Regulated in Multiple Sclerosis Patients Treated with Interferon β-1a

Abstract: Background/Aims: Multiple sclerosis (MS) is a chronic inflammatory disorder of the central nervous system. Considering the role of immune system in its pathogenesis, researchers have focused on evaluation of the expression of immune-related genes or proteins in MS patients. Among proteins whose participation in inflammatory process has been documented is the receptor for advanced glycation end products (RAGE). Methods: In the present study, we compared RAGE transcript levels by means of quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Other researchers examined the association between the receptor for advanced glycation end-products (RAGE) and disease-modifying drugs [ 42 ]. Rahimi et al [ 43 ] and Asadikaram et al [ 44 ] noticed elevated levels of serum soluble RAGE in patients treated with interferon β. Moreover, Sternberg et al [ 45 ] observed that fingolimod also mediated modulation of the RAGE axis, which apparently contributed to the anti-inflammatory and neuroprotective effects of fingolimod.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers examined the association between the receptor for advanced glycation end-products (RAGE) and disease-modifying drugs [ 42 ]. Rahimi et al [ 43 ] and Asadikaram et al [ 44 ] noticed elevated levels of serum soluble RAGE in patients treated with interferon β. Moreover, Sternberg et al [ 45 ] observed that fingolimod also mediated modulation of the RAGE axis, which apparently contributed to the anti-inflammatory and neuroprotective effects of fingolimod.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, in patients with MS who underwent CinnoVex (IFNβ-1a) or fingolimod (sphingosine-1-phosphate receptor modulator) treatments, the levels of soluble RAGE were increased, which corresponded to a positive treatment response, emphasizing the possible role of soluble RAGE in reducing neuroinflammation in affected tissue, thus diminishing the signs and symptoms of the disease. 31,32 Despite the fact that studies on the use of soluble RAGE as a specific marker of ALS progression are still in the early stages, based on evidence derived from our and other recent translational studies demonstrating the involvement of RAGE in the pathogenesis of ALS, we might assume that measuring RAGE level, especially in conjunction with AGE and AOPP, could be a prognostic marker of ALS progression. Our study demonstrated that blocking RAGE signaling with soluble RAGE delays the progression of the disease and slows down the motor function decline.…”
Section: Discussionmentioning
confidence: 97%
“…Another investigation by Gholamreza Asadikaram and colleagues in 2016 found that the mRNA expression levels of S100A12 were dramatically lowered in untreated new cases of RRMS 27 . Mahnoosh Rahim's study found that patients treated with interferon 28 had higher levels of S100A12 gene expression 28 .…”
Section: Discussionmentioning
confidence: 98%